The Influence of Discipline, Motivation, and Compensation on Employee Performance at PT Mesitecmitra Purnabangun in The Conditions of The Covid-19 Pandemic - Farhani, Hilma; Raihan; Sukamto, Bambang; Sekarini, Ratih Ayu; Derasani, Evita (CV ODIS, 2024)
The COVID-19 virus has had a major effect on conditions in Indonesia, one of which is the effect that employee performance in every company changes in the work process. All agencies are implementing the work-from-home program to change work arrangements as one of the government's guidelines for preventing COVID-19. WFH is a type of work style with the concept of a remote work system, offices are only allowed to employ 25% of employees and 75% of employees who carry out Work from Home PT Mesitecmitra Purnabangun has established a WFH program by holding meetings, briefings, and joint activities through Zoom meetings but some work cannot be done at home, such as file integrity checks or service requests that need to be done in person. Of course, this sudden policy becomes a challenge for employees on changes in performance in the office, especially discipline, motivation and compensation of employees. This study aims to determine the effect of discipline, motivation, and compensation on employee performance at PT Mesitecmitra Purnabangun. Sampling technique by distributing questionnaires to employees of PT Mesitecmitra Purnabangun. The results of this study indicate that discipline does not influence performance, motivation and compensation influence performance.